1986
DOI: 10.1080/00288233.1986.10417969
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fertiliser and grazing management on North Island moist hill country 3. Performance of introduced and resident legumes

Abstract: A grazing trial was conducted on 99 ha of steep, low fertility hilI country in southem Hawke's Bay, during 1975-81. There were 2 fertiliser treatments: low (LF) and high (HF) superphosphate application (plus lime on HF), and 3 grazing managements -rotational grazing by sheep (RGS) or cattle (RGC), and set stocking by sheep (SSS). A white clover (Trifolium repens L.) similar to Kent wild white, and annual suckling clover (T. dubium Sibth.) were already present in the pastures in small amounts. 'Grasslands Huia'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…It is well understood that increasing frequency ofdefoliation, as occurs under set-stocking, reduces leaf size and petiole length (Wilman & Asiegbu 1982). Lambert et al (1986) also observed that leaf size of white clover in rotationally grazed cattle swards were larger than those in swards either setstocked or rotationally grazed by sheep. Unlike the present study, they also observed slightly larger leaves on white clover grown under high compared with low fertiliser inputs and slight compared with intermediate and steep slopes.…”
Section: Comparison Of Hill Countrygenotypes With (Grasslands Huia' Amentioning
confidence: 76%
See 2 more Smart Citations
“…It is well understood that increasing frequency ofdefoliation, as occurs under set-stocking, reduces leaf size and petiole length (Wilman & Asiegbu 1982). Lambert et al (1986) also observed that leaf size of white clover in rotationally grazed cattle swards were larger than those in swards either setstocked or rotationally grazed by sheep. Unlike the present study, they also observed slightly larger leaves on white clover grown under high compared with low fertiliser inputs and slight compared with intermediate and steep slopes.…”
Section: Comparison Of Hill Countrygenotypes With (Grasslands Huia' Amentioning
confidence: 76%
“…The larger leaf size, petiole, and internode lengths of genotypes on north-facing aspects was also observed by Lambert et al (1986). Leaf sizes of white clover genotypes from dry north-facing aspects were larger than those from moist southfacing aspects in a study comparing populations from six farms (Caradus et al 1990).…”
Section: Comparison Of Hill Countrygenotypes With (Grasslands Huia' Amentioning
confidence: 91%
See 1 more Smart Citation
“…'Grasslands Huia' in the Ballantrae experiment produced considerably more DM than in the trials of Lambertet al (1986)and Chapman & Campbell (1986), also at Ballantrae, where it was oversown into pastures receiving high fertiliser inputs by comparison to this trial. Lambert et al (1986) recorded average total white clover yields ('GrasslandsHuia' plustheresidentgenotype) under sheep grazing of about 1150 kg DM/ha per year over 6 years when57 kg ofP was appliedper ha per year, and 500-550 kg DM/ha per year when only 11kg P was appliedper ha per year. On thebasisof equal fertiliser input, our results can be compared to the 11 kg P/ha per year treatmentof Lambert et al (1986).…”
Section: Discussionmentioning
confidence: 99%
“…Lambert et al (1986) recorded average total white clover yields ('GrasslandsHuia' plustheresidentgenotype) under sheep grazing of about 1150 kg DM/ha per year over 6 years when57 kg ofP was appliedper ha per year, and 500-550 kg DM/ha per year when only 11kg P was appliedper ha per year. On thebasisof equal fertiliser input, our results can be compared to the 11 kg P/ha per year treatmentof Lambert et al (1986). However, the 500--550 kg DM/ha per year cited above from Lambert et al (1986) is an average for a range of slope and aspect combinations, which includes relatively fertile and moist sites of gentle slope « 12°).…”
Section: Discussionmentioning
confidence: 99%